Techno-economic analysis and environmental impact of electric vehicle - Pg Abas A.E.; Yong J.; Mahlia T.M.I.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Commerce; Conversion efficiency; Cost benefit analysis; Costs; Economic analysis; Environmental impact; Exhaust systems (engine); Gas emissions; Gasoline; Greenhouse gases; Life cycle; Renewable energy resources; Electric Vehicles (EVs); Financial incentives; Hybrid electric vehicles (HEVs); Internal combustion engine vehicles; Life cycle costs (LCC); Power plant efficiency; Renewable energy source; Techno-Economic analysis; Hybrid vehicles